PENGARUH SLACK RESOURCES, UKURAN PERUSAHAAN, DEWAN KOMISARIS DAN LIPUTAN MEDIA TERHADAP PENGUNGKAPAN TANGUNG JAWAB SOSIAL PERUSAHAAN - Melvin Melvin (Jurnal Widya Akuntansi dan Keuangan, 2021)
CSR disclosure, which is information on social responsibility activities that have been carried out by the company and is reported in annual reports and sustainability reports. In this study, the objective of this research is to analyze the effect of slack resource, company size, board size and media coverage on CSR disclosure. CSR disclosure itself in this study is the dependent variable measured using a dummy variable. This study also uses four independent variables, namely slack resources, company size, board size and the last one, media coverage. In this study, the testing and analysis techniques used were logistic regression techniques. The test results include, first, slack resource is able to influence CSR disclosure, but does not affect non-financial companies. Second, company size has a significant and positive effect on CSR disclosure, but has no effect on financial companies. Third, board size has a significant and positive effect on CSR disclosure. Fourth, media coverage does not have a significant and positive effect on CSR disclosure.